DIRECT TORQUE CONTROL OF THREE PHASE INDUCTION MOTOR BY USING FOUR SWITCH INVERTER - Mr. Aniket C. Daiv. (International Journal of Innovations in Engineering Research and Technology, 2021)
Induction motor proved its importance, since its invention and has been used in industry extensively as it offers advantages e.g. robust, maintenance free and satisfactorily efficiency. With the invention in semiconductor technology and three phase inverter as this plays important role for speed control of motor driver. Traditionally 6 switch, 3 phase inverters are used extensively for controlling speed for motors. This may involves losses occurring in the six switches, and the complexity also increases forcontrol algorithms and interface circuits for implementation PWM logic signals.